1996
DOI: 10.1097/00005110-199602000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Valuing Authority/Responsibility Relationships

Abstract: Central to the practice of professional nursing are the elements of accountability, autonomy, direct communication, and authority. The value that nursing work groups place on authority affects their level of acceptance of responsibility and accountability for clinical decision making. The authors examined the value that nurse managers and staff nurses on primary nursing and total patient care units place on authority/responsibility relationships. Results indicated that nurse managers and staff nurses on primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…These findings may reflect the perception of inadequate support that was evident in the .40*** *N/S, **P = 0.05, ***P = 0.000. qualitative data, the manifestation of the resistance to change, or it could be indicative of the differences in values and beliefs between administration and the nursing staff. Webb et al (1996) suggest that a lack of congruency between the values and beliefs of management and nurses may result in deliberate manoeuvres by some nurses to thwart the success of any change. Garon et al (2009) concluded that peer and management support were crucial to nursing staff during changes in nursing practice.…”
Section: Discussionmentioning
confidence: 99%
“…These findings may reflect the perception of inadequate support that was evident in the .40*** *N/S, **P = 0.05, ***P = 0.000. qualitative data, the manifestation of the resistance to change, or it could be indicative of the differences in values and beliefs between administration and the nursing staff. Webb et al (1996) suggest that a lack of congruency between the values and beliefs of management and nurses may result in deliberate manoeuvres by some nurses to thwart the success of any change. Garon et al (2009) concluded that peer and management support were crucial to nursing staff during changes in nursing practice.…”
Section: Discussionmentioning
confidence: 99%
“…Integrative mechanisms, such as coordination within and across units and strong communication mechanisms, promote effective accomplishment of work and result in greater satisfaction and organizational commitment for both senior leaders and their subordinates (Relf 1995;Rose and Reynolds 1995;Webb et al 1996). The quality of manager-subordinate communication is strongly related to subordinate job satisfaction (Pincus 1986;Prescott and Bowen 1987).…”
Section: Conceptual Modelmentioning
confidence: 99%
“…In seven studies (i.e. Fleeger 1993, Grzyb-Wysocki & Enriquez 1996, Webb et al 1996, Jones et al 1997 (Smircich 1983). Comparable to root metaphor perspective, or culture is something an organization is (Smircich 1983).…”
Section: Unit Of Analysismentioning
confidence: 99%
“…The instrument is designed to diagnose organizational ideology Instrument item examples: not available Robustness: good face validity Nursing Unit Cultural Assessment Tool, NUCAT (Coeling & Simms 1993a) Four articles (e.g. Coeling & Simms 1993b, Rizzo et al 1994, Goodridge & Hack 1996, Webb et al 1996 Consists of 50 (NUCAT-2 and NUCAT-3) or 55 (NUCAT) different cultural behaviours that are indicators of behaviours that are important to practicing nurses and that differ between units. Using a four-(NUCAT-2), five-(NUCAT-3) or six-point (NUCAT) Likert scale respondents rate behaviours that they prefer vs. those they believe occur typically on their unit* Instrument item examples: How important is it to work in an efficient manner?…”
Section: Taking Stockmentioning
confidence: 99%